MUDA DAN MEMIMPIN: REFLEKSI YOUTH LEADERSHIP DALAM KISAH YUSUF DALAM ALKITAB DAN RELEVANSINYA BAGI GENERASI MILENIAL - Sandiki, Reza; Widianto, Alwi; Zelig, Eric (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2025)
This article analyzes the characteristics and leadership values of young biblical figures and their relevance for the millennial generation in the modern era. Using a qualitative approach and literature review, this research examines the stories of Joseph, David, Daniel, Mary, and Timothy as examples of young leaders who faced challenges and demonstrated leadership values that can serve as inspiration. The findings indicate that values such as integrity, courage, wisdom, obedience, and empowerment are highly relevant in shaping authentic Christian leadership in the digital and global era. This article offers recommendations for churches and Christian educational institutions in nurturing young leaders who are equipped to address the challenges of contemporary times.